1987
DOI: 10.1080/01435698.1987.9752828
|View full text |Cite
|
Sign up to set email alerts
|

Edaphic Component of the Environmental Degradation Resulting From the Replacement of Tropical Rain Forest by Field and Tree Crops in Sw Nigeria

Abstract: Mature tropical rain forest is in a state of dynamic equilibrium with its soil, micro-and macro-climate. Data collected in the cocoa producing areas of SW Nigeria show that when this forest is removed and replaced by field or tree crops, the balance between vegetation and soil breaks down, and this leads to instability and a considerable deterioration in soil quality. An index of soil deterioration ~as derived and showed the following percentage declines for field and tree crops respectively: bulk density, 28%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Allen (1985) observed that reduction in CEC was 50% higher in the tropical soils than in temperate soils under deforestation. Adejuwon and Ekanade (1987) also reported the losses of 34%-36% in CEC and 19%-50% in exchangeable Ca 2+ , Mg 2+ , Na + and K + in the tropical region due to deforestation.…”
Section: Exchangeable Bases and Cation Exchange Capacitymentioning
confidence: 93%
“…Allen (1985) observed that reduction in CEC was 50% higher in the tropical soils than in temperate soils under deforestation. Adejuwon and Ekanade (1987) also reported the losses of 34%-36% in CEC and 19%-50% in exchangeable Ca 2+ , Mg 2+ , Na + and K + in the tropical region due to deforestation.…”
Section: Exchangeable Bases and Cation Exchange Capacitymentioning
confidence: 93%
“…Arbuscular Mycorrhizal Fungi (AMF -phylum Glomeromycota) are known to have a key role in terrestrial ecosystems as they contribute to improve plant nutrition, particularly uptake of low mobility nutrients from soil solutions such as P, Zn, and ultimately Cu, to increase plant resistance to drought, salinity and tolerance to pathogens and to improve soil structure [1,2]. However, disturbances can affect several aspects of AMF communities in both agricultural and natural ecosystems through the process of limiting organic inputs into the soil and biomass removal [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Nutrient losses have been reported as a major challenge in cocoa cultivation. Several researchers found significant declines in soil organic matter and in all major nutrients under cocoa when compared with soils under forest [12][13][14]. Harvesting nutrient-rich biomass and exporting it lead to depletion of soil nutrients or nutritional imbalance affecting the following crop [15].…”
Section: Introductionmentioning
confidence: 99%